Tietze Syndrome in A Female POST-COVID-19 Infection: A Review of Current Understanding and Ultrasound Diagnosis - Sun Yang, Li Mofan, Wang Shumin (Advanced Ultrasound in Diagnosis and Therapy)
Tietze syndrome which refers to painful non-purulent inflammation of the costal cartilage or sternoclavicular joint is a rare disease that is poorly reported. We report a case of Tietze syndrome in a 52-year-old female with sternoclavicular joint pain and chest wall mass post-COVID-19 virus infection. She suffered pain and swelling in the left sternoclavicular joint, which were relieved after hot compress. This case is the first report on Tietze syndrome post-COVID-19 virus infection in China. We report this case to improve our understanding of this disease and discuss possible mechanism from the perspective of embryology and pathology.